ANALISIS FAKTOR PAJAK DAN FAKTOR LAIN YANG BERPENGARUH TERHADAP TINGKAT HUTANG PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE TAHUN 2010-2012 - Diana Panca Wardani, 09.05.52.0169; Kartika, Andi (Students Journal of Accounting and Banking, 2014)
This study aims to determine the factor analysis of tax and financial factors which affect the level of debt. The population in this studyis a manufacturing company that is listed on the Indonesia Stock Exchange 2010-2012. The samples in this study were taken by purposive sampling method. Data were analyzed using skewness normality test, the classical assumption, koofisien determinasi test, F-test and test hypotheses. The result of this study is the effect on leverage is corporate tax, profitability and past debt, IOS where as no effect on leverage is non-debt tax shield and tax shield.Keywords: corporate tax rate, non-debt tax shield, IOS, Profitability, Tax Shield, past debt, leverage